Investigating the link between engagement, readiness, and satisfaction in a synchronous online second language learning environment. (April 2022) - Ji, Hyangeun; Park, Soyeon; Shin, Hye Won
Abstract: Despite the increasing number of synchronous online learning studies examining the links between engagement, readiness, and satisfaction, to the best of our knowledge, no previous research has focused on investigating second language (L2) learners' satisfaction in a synchronous online learning environment at two waves of data collection. The present study examines this issue by conducting a measurement at the beginning and toward the end of the semester on a sample of 82 Korean undergraduate students using self-report assessments. This study further explored the ways in which students engage in an online synchronous learning environment using qualitative data. Ordinary least squares regression analysis was utilized to examine the predictive relationships between engagement, readiness, and satisfaction. The results showed that higher readiness was associated with positive satisfaction levels at the start of the semester, while learner engagement predicted higher satisfaction levels toward the end of the course. Moreover, students' use of learning strategies such as note-taking, recording, and searching for additional materials increased their engagement, strengthening the positive relationship between engagement and satisfaction. These findings suggest that L2 learner engagement can effectively facilitate increases in satisfaction in synchronous remote learning over the course of a semester.